平衡计分卡在行政执法机关的应用调适 ：以伊犁州工商行政管理局为例 = The application and adaptation of balanced scorecard in law enforcement agencies : a case study of Yili industrial and commercial administration bureau - 高建东 Gao, Jiandong (2011)
平衡计分卡自创立以来，就对企业界和政府机构产生了巨大的影响力和强烈的冲击力。平衡计分卡是全面的绩效评价系统，是全面的战略管理系统，是系统的沟通工具，是上世纪管理思想的集大成者。平衡计分卡被《哈佛商业评论》评为75年来最具有影响力的战略管理工具，70%以上《财富》杂志公布的世界1000强企业采用了平衡计分卡系统，西方许多国家也将平衡计分卡导入政府管理系统，取得了显著的绩效管理成果。 Balanced Scorecard since its inception to businesses and government agencies on had a huge influence and a strong impact. Balanced Scorecard is a comprehensive performance evaluation system is a comprehensive strategic management system, a system of communication tools, is the last century, a master of management thinking. Balanced Scorecard is "Harvard Business Review" as the most influential 75 years of strategic management tool, 70% of "Fortune" magazine published by Global 1000 enterprises to adopt the Balanced Scorecard system, many Western countries will also be balanced scorecard into the government management system, has achieved remarkable performance management results.